Variations in Patient Portal Adoption in Four Primary Care Practices - Wald, Jonathan S. (American Medical Informatics Association, 2010)
This case report reviews the patient portal adoption experiences of four primary care practices at Partners HealthCare during 2002 – 2009. Although each practice used the enterprise patient portal (Patient Gateway) and electronic health record, their patient enrollments varied substantially, as did their marketing approaches, new feature adoption, leadership approach, and staff involvement. Marketing limitations, leadership concerns, and limited staff engagement characterized the low-enrollment practices, but not the others. These factors, along with other practice characteristics such as location and patient demographics, should be explored in future research to identify best practices for successful adoption of a patient portal.